The Selection of Preschool for Immigrant and Native-born Latino Families in the United States - Ansari, Arya (Early Child Res Q, 2017)
With the national push to expand preschool education, there has been growing interest in understanding why Latino families are enrolled in preschool at lower rates than non-Latino families. This study applied the accommodations model by Meyers and Jordan (2006) to the Early Childhood Longitudinal Study-Birth Cohort (n = 5,850) to provide a more nuanced understanding of the preschool selection of U.S.- and foreign-born Latino families. Results from this investigation underscored the similarities and differences that existed in the selection behaviors of different groups of families, while also highlighting important differences within the Latino population. In general, these differences within the Latino population cut across community language use, child factors, and parents’ beliefs about school readiness. Moreover, after accounting for the various selection factors, there were no longer any consistent differences in the preschool enrollment rates between Latino children and their Black and White peers. When taken together, these findings suggest that careful attention must be paid to the heterogeneity in the experiences of Latino families in navigating the preschool market.